EXPLORING THE ALLURE OF STRAWBERRIES - ZAHRA, NASEEM; SAEED, MUHAMMAD KHALID; FATIMA, NOOR; SHEHZAD, EZZA; SAEED, ASMA (Innovare Journal of Agricultural Sciences, 2023)
Strawberry is a member of family Rosaceae. Fragaria x ananassa are two important species which grown throughout the world. It is a rich source of Vitamin C, also contains sugar, organic acid, and major constituent is water. It is utilized in fresh form as well as processed such as jam and juices. Organic food products are beneficial for the people around the globe. From the past years, organic food production is increased abruptly. Plasticulture strawberry production system is used which enhances the yield of strawberry doubles times as compared to matted rows. Different kinds of plastic mulches used which give protection to plant and soil and increase the yield. As we know due to health concerns that occurred due to excessive use of chemicals and fertilizers, it is hazardous to use chemical fertilizers on unpeelable fruits like strawberry. It enhances risks for human health. Many constituents of strawberries such as ellagic acid, anthocyanins, and ellagitannins provide different health benefits to humans. It has anticarcinogenic and anti-antioxidant properties, and they prevent human from heart diseases and many other problems such as obesity.